Identificação e caracterização parcial de antígenos isolados de vacinas contra Leishmaniose tegumentar americana (Leishvacin ) - Wanderley Almeida Ferreira (2002)
This work concerns with the aim of to isolate antigens from a vaccine against American Tegumentar Leishmaniasis (ATL), of long storage time (Leishvacin). These vaccines present high grade of degradation upon storage, but are able to protect human individuals against ATL; some after have been storage by many years. Antigens were isolated from polyvalent vaccine (PI antigen) and from monovalente ones of the strain Leishmania amazonensis (P8 antigen), by two fractionating methods (dialysis and chromatography). PI and P8 antigens, isolated by chromatographic methods, are molecules of highly molecular weight, formed by complexes aggregation phenomena involving low molecular weight molecules. Both antigens display specific reactivity against sera from American humans and dogs suffering of visceral leishmaniasis (AVL). These antigens not showed cross-reactivity with sera from individuals with other forms of the leishmaniasis or disease related ones. Not cross-reactivity between PI and P8 antigens with sera of healthy humans or healthy dogs was observed, indicating that these antigens could be used in diagnostic assays to leishmaniasis. Chemical analysis showed that PI and P8 antigens are sensible to sodium dodecyl sulphate, periodic acid and 2-mercaptoethanol treatment, being that two latter chemicals agents abolish the reactivity of these antigens with AVL sera. All these treatments deaggregate the molecular structure of PI and P8 antigens, but by different mechanisms. Chemical and analytical methods discarded the presence of any moiety protein or nucleic acids ones in the structure of these antigens. However, carbohydrate was detected by chemical or analytical analysis as some major component of PI and P8 antigens. The antigens PI and P8 isolated of vaccines against ATL are, therefore, antigenic aggregates formed by the aggregation of small saccharides or oligosaccharides. These antigens are composed plausibly by glucose, galactose, manose, and by some forms of saccharide derivatives (phosphate, sulpho and amino sugars). The results of this study indicates early changes in molecular composition of the vaccines against ATL (Leishvacin), independent of the storage. Among these changes are relevant: i) the high degradation grade of the molecules initially present in vaccine, ii) formation of high molecular structures by aggregations phenomena, iii) recognizing of these antigenic aggregates specifically by sera to AVL patients and dogs but not by ATL sera from ones, iv) these antigenic aggregates are essentially constituted by carbohydrates.